Participatory Practices in Art and Cultural Heritage Learning Through and from Collaboration - Rausch, Christoph; Benschop, Ruth; Sitzia, Emilie; van Saaze, Vivian (Springer International Publishing, 2022)
This edited volume analyzes participatory practices in art and cultural heritage in order to determine what can be learned through and from collaboration across disciplinary borders. Following recent developments in museology, museum policies and practices have tended to prioritize community engagement over a traditional focus on collecting and preserving museal objects. At many museal institutions, a shift from a focus on objects to a focus on audiences has taken place. Artistic practices in the visual arts, music, and theater are also increasingly taking on participatory forms. The world of cultural heritage has seen an upsurge in participatory governance models favoring the expertise of local communities over that of trained professionals. While museal institutions, artists, and policy makers consider participation as a tool for implementing diversity policy, a solution to social disjunction, and a form of cultural activism, such participation has also sparked a debate on definitions, and on issues concerning the distribution of authority, power, expertise, agency, and representation. While new forms of audience and community engagement and corresponding models for "co-creation" are flourishing, fundamental but paralyzing critique abounds and the formulation of ethical frameworks and practical guidelines, not to mention theoretical reflection and critical assessment of practices, are lagging. This book offers a space for critically reflecting on participatory practices with the aim of asking and answering the question: How can we learn to better participate? To do so, it focuses on the emergence of new norms and forms of collaboration as participation, and on actual lessons learned from participatory practices. If collaboration is the interdependent formulation of problems and entails the common definition of a shared problem space, how can we best learn to collaborate across disciplinary borders and what exactly can be learned from such collaboration?
Keywords: Geschichte 1900-2022; Sources and Subjects of International Law, International Organizations; Theories of Law, Philosophy of Law, Legal History; Human Rights; Cultural Heritage; Cultural Resource Management; Visual Culture; International law; Law-Philosophy; Law-History; Human rights; Cultural property; Cultural property-Protection; Culture-Study and teaching; Kulturgüterschutz; Kunst; Partizipation; Denkmalpflege